Konsep Penanganan Bencana Banjir pada Perumahan Perumnas Manggala Kota Makassar - Mimi Arifin; Abdul Rachman Rasyid; Ananto Yudono; Shirly Wunas; Slamet Trisutomo; M. Yamin Jinca; Mukti Ali; Ihsan -; Arifuddin Akil; Wiwik Wahidah Osman; Yashita Kumala Dewi Sutopo; Sri Aliah Ekawati; Muhammad Fathien Azmy; Gafar Lakatupa; Sri Wahyuni; Laode Muhammad Asfan Mujahid; Jayanti Mandasari; Suci Anugrah Yanti; Andi Nada Zahirah; Isratilla Natasya; Ninik Dwi Resky; Ana Dian Ayu (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
Perumnas Manggala or known as Perumnas Antang Block 10 is one of the housing and settlement areas that are prone to flooding. The purpose of this community service activity is to socialize flood disaster management by first identifying the characteristics of the causes of flooding and developing a concept with the community regarding flood management in residential areas. Methods of implementing community service. The data collection techniques are observation, documentation, and interviews, while the data analysis techniques are descriptive qualitative, and spatial analysis. The data collected is used in drafting the concept of flood management in the form of socialization and discussions with the community, community leaders, and the academic community. The results of service activities are in the form of the concept of flood management through preventive efforts to minimize flood disasters at Perumnas Antang Block 10, namely making infiltration wells, planting vegetation, managing drainage and waste systems. Adaptive and curative efforts are in the form of developing disaster response groups as preparation management in dealing with disasters that routinely occur every year. The results of the socialization show a significant level of change by the community where the level of interest in community participation and understanding of the concept of flood management increases. The community actively participates in discussions and expresses its willingness to participate in disaster mitigation activities. The discussion also showed that the community had high hopes for government assistance, both morally and materially, as well as disaster response training.